Optimalisasi Peran Dewan Pengawas Syariah Pada Lembaga Keuangan Mikro Syariah (Studi Kasus di Assosiasi Koperasi Warga NU Jepara) - Nuha, Ulin (MALIA: Journal of Islamic Banking and Finance, 2018)
This study aims to find out the supervision carried out by the Sharia Supervisory Board, and try to analyze the role and function of the Sharia Supervisory Board in supervising shari'ah financial institutions, especially for ASKOWANU Jepara. This research is descriptive qualitative research, where data collection is carried out from various sources in the form of books, magazines, newspapers and documents related to the supervision of sharia financial institutions.The results of this study illustrate that basically the supervision of sharia financial institutions has two systems, namely supervision of aspects: (i) financial conditions, compliance with the provisions of financial institutions in general and prudential principles, and (ii) compliance with sharia principles in the operational activities of institutions Islamic finance. In this regard, the structure of supervision of sharia financial institutions is more multilayer in nature, which would ideally consist of a system of internal supervision carried out by Sharia Supervisory Board, which is more in-depth and carried out so that there are mechanisms and control systems for the interests of management and external supervision systems. by DSN which basically to meet the interests of customers and public interests in general.